Pengaruh Penghapusan Ujian Nasional Terhadap Motivasi Belajar Perserta Didik Di Masa Pandemi - Ghani, Salakhuddin; Zharfa, Mustafid (Yayasan Darussalam Bengkulu, 2020)
This research is titled THE EFFECT OF ELIMINATION OF NATIONAL EXAMINATION ON LEARNING MOTIVATION OF STUDENTS IN THE PANDEMIC PERIOD. The National Examination is used to evaluate education on a national scale. However, the elimination of the National Examination will have an impact on students' motivation to learn. This study aims to determine the effect of eliminating the National Examination on students' learning motivation. This research is a descriptive qualitative research by collecting data through questionnaires, interviews and documentation. This research was conducted at MI NU Sabilul Ma'arif Islamiyah Klumpit Gebog Kudus with a sample of sixth grade students in the 2019-2020 academic year. The results of this study are quite significant results between the elimination of the National Examination with the motivation of students to learn, learning motivation of students increased from the previous UN eliminated by a difference of 12,81%, from an average of 70,60 % before the National Examination dropped to the number 57,79% at the time of UN abolition, and depends on the medium category.